EKSPLORASI MINERAL MANGAN MENGGUNAKAN METODE POLARISASI TERINDUKSI DI DAERAH SUANAE, KECAMATAN MIOMAFO BARAT, KABUPATEN TIMOR TENGAH UTARA, NUSA TENGGARA TIMUR - , AG. PRIYA EKA A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A geophysicals survey for mangan by using IP has been carried at Suanae area, Kecamatan Miomafo Barat, Kabupaten Timor Tengah Utara, Nusa Tenggara Timur. Geologically , the survey area is located in Mutis Complex. The objective is to determine the distribution of the manganese and to estimate potential reserves. Induced polarization measurements is conducted in time domain with dipole â dipole configuration . This measurement was done in 22 lines. Interval is 30 meters between lines and 20 meters between electrodes. The tools used are Syscal Jr Switch - 48. From the survey, the results obtains 2D cross sections indicating the presence of the manganese in clays. Resistivity is 0 - 40 ohm.meter and chargeability is 80 - 170 milliseconds. The thresholds are used to create 3D models. Manganese reserve estimation is 690. 875 m3.